Effect of fluoride ions modifier and ceramic Al2O3 particles additives on plasma electrolytic oxidation of AZ31. (3rd October 2017) - Soliman, H.; Hamdy, A. S.
ABSTRACT: Plasma electrolytic oxidation (PEO) process is proved to be an effective technique for forming highly protective oxide film on Mg alloy AZ31. A comparative study has been done to investigate the PEO films deposited from silicate solution with NaF, Al2 O3 nano-additives. The surface morphology feature, phase composition and elemental composition were examined by field scanning electron microscope, energy dispersive X-ray, X-ray diffraction. Doping of additives showed an obvious effect mainly on the peak of MgO and the thickness of the PEO films. Fluoride has a promising role and its presence considerably resulted in thicker and compacter films with improved corrosion resistance. Vice versa unexpected negative results had been obtained in the presence of alumina additives. It is assumed that fluoride ions enhanced ions conductivity during PEO process therefore promoted the film growth rate. On the other hand, the bulk Al2 O3 particles hindered the ions movement through the coating deposition leading to thinner less compact films formation.